Representation of Racism in the Film "Till" - Stara Asrita; Muhammad Syah Tegar Alreswara; Deani Prionazvi Rhizky (Journal of Content and Engagement, 2023)
The purpose of this study is to answer how signifier and signified are displayed in the film "Till" and what are the representations of racism contained in the film "Till". The data studied is in the form of pieces of images, sounds, text or sounds contained in the film "Till". This study is using Saussure's semiotics. It will help analyse media texts with a set of signs that have various meanings. The result of this study shows that the film "Till" contains acts of racism based on Henry and Tator's theory in the form of Individual Racism and Systemic Racism. This theory is divided from Internalized Racism, Interpersonal Racism, Institutional Racism and Structural Racism. Researchers examine each component of the types of racism such as reactions, associations, perspectives, identity, labelling, stereotypes, separatism, and discrimination.